7A.01: INCREASED RISK OF MORTALITY IN OBESE PATIENTS WITH HIGH NOCTURNAL BLOOD PRESSURE VARIABILITY. RESULTS FROM THE ABP-INTERNATIONAL STUDY. (June 2015) - Palatini, P.; Reboldi, G.P.; Beilin, L.; Casiglia, E.; Eguchi, K.; Imai, Y.; Kario, K.; Ohkubo, T.; Pierdomenico, S.D.; Schwartz, J.E.; Wing, L.; Verdecchia, P.
Abstract : Objective: The association between obesity and all-cause mortality is controversial and may differ according to subjects' characteristics. Blood pressure variability (BPV) may be increased in obese individuals and thus impair prognosis. The purpose of this study was to evaluate whether the relationship between obesity and mortality is influenced by short-term ambulatory BPV. Design and method: The analysis was performed in 8724 participants (54% men) aged 51 ± 15 years enrolled in 8 prospective studies in Australia, Italy, Japan, and U.S.A. The predictive power of obesity (BMI >=30 kg/m2) for mortality was evaluated from multivariable Cox models in the subjects stratified by high or low nocturnal BPV (above or below the median). Results: Obese participants (N = 1286) had higher age-and-sex adjusted systolic and diastolic BPV than the non-obese participants (p = 0.002/<0.001). Obese subjects with high systolic or diastolic BPV had higher nocturnal heart rate (p = 0.01/<0.001) than obese subjects with low BPV and were more frequently diabetic (p<0.001) and heavy alcohol drinkers (p < 0.001). During a median follow-up of 6.4 years there were 361 deaths, 4.7% in the obese and 4.0% in the non-obese individuals (P = NS). However, the risk of mortality among the obese subjects greatly differed according to BPV level. In Cox models including age, sex, mean ambulatory BP, smoking, alcohol use, diabetes, cholesterol, creatinine, and nocturnal heart rate, the obese group with high systolic BPV had a doubled risk of mortality compared to the non-obese group (HR, 2.0, 95%CI, 1.4–2.9, p < 0.001), whereas the risk was not increased in the obese group with low BPV (P = 0.81). Similar results were found for diastolic BPV, with a HR of 1.7 (1.2–2.5, p = 0.002) in the high BPV group and no association at all with mortality (p = 0.87) in the low BPV group. Inclusion of night-time BP dipping in the regressions did not change the strength of the associations. Conclusions: These data show that high nocturnal BPV greatly increases the risk of mortality related to obesity. High BPV is accompanied by increased heart rate and may reflect the influence of transient BP elevations related to sleep apnea and/or baroreflex dysfunction.